La relación asistencial en la atención sanitaria a embarazo y parto: aspectos éticos - Josefina Goberna-Tricas (Universitat de Barcelona, 2023)
The care relationship between healthcare professional and their patients derives from the classical model initiated in Hippocratic medicine. In 1978, the Belmont Report was published, proposing a method based on the acceptance of three basic ethical principles: a) Respect for persons, b) Beneficence, c) Justice. MATERIALS AND METHODS. This work presents an ethical reflection that aims to respond to the specific reality of maternity care, where the specificity of care directed at the mother cannot overlook the presence of a foetus intended to become a newborn.RESULTS. After analyzing the effective application of bioethical principles, the discussion revolves around the concept of «maternal-foetal conflict», presenting the deliberative model of healthcare relationships as a preferred option for respecting autonomy in the field of maternity care.CONCLUSIONS. The development of respect for the principle of autonomy within a care relationship should prioritize dialogue and respect for women's right to exercise their autonomy, understanding it in terms of singularity, contextualization, and support for each pregnancy and childbirth.